Sentiment Analysis of The Opinion of Moving The Capital City on Twitter with The Support Vector Machine Method - Hidayat, Tezza Fazar Tri; Garno, Garno; Ridha, Azhari Ali (Jurnal Ilmu Komputer; Vol 14 No 1 (2021): Jurnal Ilmu KomputerDO - 10.24843/JIK.2021.v14.i01.p06, 2021)
The relocation of the capital city of Indonesia has now been inaugurated by President Joko Widodo on August 26, 2019, to Kalimantan, it is a new history in Indonesian history because it has never happened before, giving rise to many opinions or responses from the public. Sentiment analysis is an activity used to analyze a person's opinions or opinions on a topic. Twitter is a social media used to express user's opinions and united them on a topic. Support Vector Machine is a method of text mining which includes classification methods and Term Frequency - Inverse Document Frequency is a method of weighting characters. SVM and TF-IDF can be used to analyze public opinion sentiments on the topic of moving the Indonesian capital. The purpose of this study is to classify public opinion on the topic of moving the Indonesian capital from thousands of tweets that have been collected and filtered. Tweets that have been processed are 992 tweets from March 22-29, 2020 and, consist of 221 data with positive labels and 771 negative data. And using the SVM method which has an accuracy of 77.72% and combined with TFIDF which increases its accuracy to 78.33%.